Kwestia zwrotu mienia kościelnych osób prawnych w świetle ustawy o stosunku Państwa do Kościoła Katolickiego w Rzeczypospolitej Polskiej - Pelc, Paweł (Prawo Kanoniczne, 1995)
A relation between the state and catholic church in Poland was regulated in 1989 as a result of long negotiations between communist authorities and church representatives. The legislator could not disregard the issue of property lost by church, in particular the property lost during communist time. In post-communist period 1989 Law on State Relation to Catholic Church was to some extend amended to reflect the interests of the Church. The Law of 1989 provides for two ways of resolving the church property status. If a property remained in church legal person’s possession then, in cases described in Law of 1989, title to such property (right of ownership) is granted to that person. Another way is a return of lost church property in cases specified in Law of 1989. Decisions in that matter are issued by a body called Property Commission established only for that purpose which is composed of representatives of state and church according to equality rule. Legal status of the Property Commission, various circumstances in which church was deprived of title to property, conditions of restitution of church in ownership and property are presented in details in the article. The author compares Law of 1989 with similar legal regulations adopted for other denominations in the nineties. Earlier regulations connected with return of church property are also mentioned and discussed. Author indicates and explains constitutional issnes related to this regulation.